DISPARITY OF INVESTMENT INFLOWS AMONG REGIONS IN INDONESIA - Muhammad Firdaus (Universitas Islam Indonesia, 2010)
Regions in Indonesia have been receiving investment inflows from other countries, with some regions absorb much more than the others do. This study identifies factors that influence foreign investors to come to provinces in Indonesia using a dynamic panel data approach. It investigates data on investment inflows and regional economic development indicators in each province from 1983 until 2009. The estimation results show that the General Methods of Moment system estimators are unbiased, consistent and valid. This study finds some determinants of spatial foreign investment inflows, namely market size, level of economic development, infrastructure, and education level attainment.Keywords: Disparity, investment inflows, dynamic panel data JEL classification number: F21, F23